A composite dispersant for ultrafine sand of iron tailings and preparation method thereof

By using iron tailings ultrafine sand composite dispersant composed of multi-anionic long-branch dispersant and multi-cationic long-branch dispersant, the problem of insufficient dispersion performance of iron tailings powder in the prior art is solved, and efficient dispersion and low-cost application are achieved.

CN119409437BActive Publication Date: 2025-04-01TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510018603.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-01
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing iron tailings powder dispersants have shortcomings in their dispersion performance, making it difficult to effectively disperse iron tailings powder, resulting in high water absorption and difficulty in applying it to building materials and backfill fields.

Method used

Iron tailings ultrafine sand composite dispersant is used, which consists of a multi-anionic long-branch dispersant and a multi-cationic long-branch dispersant. Through specific formulations and preparation methods, a composite dispersant can effectively disperse iron tailings powder.

Benefits of technology

It is achieved that the iron tailings ultra-fine sand composite dispersant has an ultra-high dispersion effect under low dosage, which greatly reduces the application cost and improves the fluidity of the tailings slurry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409437B_ABST
    Figure CN119409437B_ABST
Patent Text Reader

Abstract

The invention provides an iron tailings ultrafine sand composite dispersant and a preparation method thereof, wherein the iron tailings ultrafine sand composite dispersant is made of the following raw materials in parts by weight: 60-120 parts of allyl polyoxyethylene ether, 1.6-4 parts of peroxide initiator, 2-10 parts of unsaturated organic acid, 0.1-5 parts of phosphate unsaturated monomer, 0.1-5 parts of sulfonic acid unsaturated monomer, 2-10 parts of cationic unsaturated monomer, 2-5 parts of nonionic unsaturated monomer, 0.1-0.4 parts of reducing agent, and 0.2-0.8 parts of chain transfer agent. The iron tailings ultrafine sand composite dispersant of the invention still has an ultra-high dispersion effect when the dosage is low, which greatly reduces the application cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of concrete, and in particular relates to an iron tailings ultrafine sand composite dispersant and a preparation method thereof. Background Art

[0002] The mineral components of iron tailings powder are mainly quartz, hematite and goethite, and also contain some layered silicate substances. Moreover, the particles are all below 0.075mm, and the specific surface area is relatively high. Under the action of electric charge, it is very easy to form a heterogeneous agglomerate, resulting in high water absorption of iron tailings powder, which is difficult to disperse. The development of dispersants can break up heterogeneous agglomerates, release the encapsulated free water, and improve the fluidity of tailings slurry, which is of great significance for the resource utilization of tailings in building materials, backfilling and other directions. At present, sodium humate, sodium hexametaphosphonate and other substances are often used to disperse iron tailings, but their dispersibility is limited and the dosage is large. Summary of the invention

[0003] In view of this, the present invention aims to overcome the defects in the prior art and proposes a composite dispersant for ultrafine sand of iron tailings and a preparation method thereof.

[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0005] A composite dispersant for ultrafine sand of iron tailings, which is made of the following raw materials in parts by weight:

[0006] Allyl polyoxyethylene ether 60-120 parts,

[0007] Peroxide initiator 1.6-4 parts,

[0008] 2-10 parts of unsaturated organic acid,

[0009] Phosphate unsaturated monomer 0.1-5 parts,

[0010] 0.1-5 parts of sulfonic acid unsaturated monomer,

[0011] 2-10 parts of cationic unsaturated monomer,

[0012] 2-5 parts of nonionic unsaturated monomer,

[0013] Reducing agent 0.1-0.4 parts,

[0014] Chain transfer agent 0.2-0.8 parts.

[0015] Furthermore, the iron tailings ultrafine sand composite dispersant includes a polyanionic long-chain branched dispersant and a polycationic long-chain branched dispersant;

[0016] The polyanionic long-chain branched dispersant is made from the following raw materials in parts by weight:

[0017] Allyl polyoxyethylene ether 30-60 parts,

[0018] Peroxide initiator 0.8-2 parts,

[0019] 2-10 parts of unsaturated organic acid,

[0020] Phosphate unsaturated monomer 0.1-5 parts,

[0021] 0.1-5 parts of sulfonic acid unsaturated monomer,

[0022] Reducing agent 0.05-0.2 parts,

[0023] Chain transfer agent 0.1-0.4 parts;

[0024] The polycationic long-chain branched dispersant is made from the following raw materials in parts by weight:

[0025] Allyl polyoxyethylene ether 30-60 parts,

[0026] Peroxide initiator 0.8-2 parts,

[0027] 2-10 parts of cationic unsaturated monomer,

[0028] 2-5 parts of nonionic unsaturated monomer,

[0029] Reducing agent 0.05-0.2 parts,

[0030] Chain transfer agent 0.1-0.4 parts.

[0031] Furthermore, the molecular weight of the allyl polyoxyethylene ether is 4000-5000.

[0032] Furthermore, the peroxide initiator is at least one of hydrogen peroxide, ammonium persulfate or potassium persulfate; the concentration of the hydrogen peroxide is 15-35%; the unsaturated organic acid is at least one of acrylic acid, itaconic acid, maleic acid or fumaric acid; the phosphate unsaturated monomer is at least one of vinyl phosphate, 2-hydroxyethyl methyl acrylate phosphate or blocked amide phosphate; the sulfonic acid unsaturated monomer is vinyl sulfonic acid and / or 2-acrylamide-2-methylpropane sulfonic acid; the reducing agent is at least one of Vc, ferrous sulfate or sodium bisulfite; and the chain transfer agent is mercaptoethanol and / or mercaptopropionic acid.

[0033] Furthermore, the cationic unsaturated monomer is dimethyldiallylammonium chloride and / or methyl-acryloyloxyethyltrimethylammonium chloride; and the nonionic unsaturated monomer is acrylamide and / or N,N-dimethylacrylamide.

[0034] The method for preparing the composite dispersant of ultrafine sand of iron tailings comprises the following steps:

[0035] Step 1 is to prepare a polyanionic long-chain branched dispersant: allyl polyoxyethylene ether and a peroxide initiator are added to deionized water, and mixed evenly to obtain a first kettle bottom mixed liquid; unsaturated organic acid, phosphate unsaturated monomer, sulfonic acid unsaturated monomer, reducing agent and chain transfer agent are added to deionized water, and mixed evenly to obtain a polyanionic dropwise solution; under stirring, the polyanionic dropwise solution is added dropwise to the first kettle bottom mixed liquid, and the polyanionic long-chain branched dispersant is obtained after heat preservation;

[0036] Step 2 is to prepare a polycationic long-chain branched dispersant: allyl polyoxyethylene ether and a peroxide initiator are added to deionized water, and mixed evenly to obtain a second kettle bottom mixed liquid; a cationic unsaturated monomer, a nonionic unsaturated monomer, a reducing agent and a chain transfer agent are added to deionized water, and mixed evenly to obtain a polycationic dropwise solution; under stirring, the polycationic dropwise solution is added dropwise to the second kettle bottom mixed liquid, and the polycationic long-chain branched dispersant is obtained after heat preservation;

[0037] Step 3 is to mix the polyanionic long-chain branched dispersant with the polycationic long-chain branched dispersant to obtain the iron tailings ultrafine sand composite dispersant.

[0038] Further, in step 1, in the process of preparing the first kettle bottom mixed liquid, the mass ratio of allyl polyoxyethylene ether, peroxide initiator and deionized water is 30-60:0.8-2:30-100; in step 1, in the process of preparing the polyanion dropwise liquid, the mass ratio of unsaturated organic acid, phosphate unsaturated monomer, sulfonic acid group unsaturated monomer, reducing agent, chain transfer agent and deionized water is 2-10:0.1-5:0.1-5:0.05-0.2:0.1-0.4:10-30.

[0039] Furthermore, in step 2, during the preparation of the second kettle bottom mixed liquid, the mass ratio of allyl polyoxyethylene ether, peroxide initiator and deionized water is 30-60:0.8-2:30-100; in step 2, during the preparation of the polycationic dropwise liquid, the mass ratio of cationic unsaturated monomer, nonionic unsaturated monomer, reducing agent, chain transfer agent and deionized water is 2-10:2-5:0.05-0.2:0.1-0.4:10-30.

[0040] Furthermore, the rotation speed of the stirring step in step 1 is 400-1500r / min, the time of the dropping step is 1.5-3.5 hours, and the time of the insulation step is 2 hours; the rotation speed of the stirring step in step 2 is 400-1500r / min, the time of the dropping step is 1.5-3.5 hours, and the time of the insulation step is 2-3 hours.

[0041] Furthermore, in the step 3, the mass ratio of the polyanionic long-chain branched dispersant to the polycationic long-chain branched dispersant is 1-10:1.

[0042] Compared with the prior art, the present invention has the following advantages:

[0043] The iron tailings ultrafine sand composite dispersant of the present invention still has an ultra-high dispersing effect when the dosage is relatively low, thereby greatly reducing the application cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 is the XRD diagram of the ultrafine iron tailings sand of the present invention;

[0045] Figure 2 This is a schematic diagram of the structure of the composite dispersant for ultrafine sand of iron tailings according to Example 1 of the present invention;

[0046] Figure 3 Schematic diagram of the dispersion mechanism of the composite dispersant for ultrafine sand of iron tailings according to Example 1 of the present invention;

[0047] Figure 4 Schematic diagram of the dispersion mechanism of the zwitterionic long-chain branched dispersant described in Comparative Example 3 of the present invention;

[0048] Figure 5 Schematic diagram of the structural comparison of the dispersant described in Example 1 of the present invention and the dispersant described in Comparative Example 4. DETAILED DESCRIPTION

[0049] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0050] The present invention will be described in detail below with reference to the embodiments.

[0051] Example 1

[0052] A method for preparing a composite dispersant for ultrafine sand of iron tailings comprises the following steps:

[0053] Step 1 is to prepare a polyanionic long-chain branched dispersant: 60g of allyl polyoxyethylene ether and 1.5g of 35% hydrogen peroxide are added to 60g of deionized water, and mixed evenly to obtain a first kettle bottom mixed liquid; 4g of acrylic acid, 2g of vinyl phosphate, 3g of vinyl sulfonic acid, 0.15g of Vc and 0.1g of mercaptoethanol are added to 30g of deionized water, and mixed evenly to obtain a polyanionic droplet; under a stirring state at a speed of 400-1500r / min, the polyanionic droplet is dropwise added to the first kettle bottom mixed liquid, and the polyanionic long-chain branched dispersant is obtained after being kept warm for 2 hours;

[0054] Step 2 is to prepare a polycationic long-chain branched dispersant: 60g of allyl polyoxyethylene ether and 1.5g of 35% hydrogen peroxide are added to 60g of deionized water, and mixed evenly to obtain a second kettle bottom mixed liquid; 5g of DMDAAC, 3g of acrylamide, 0.1g of Vc and 0.12g of mercaptoethanol are added to 30g of deionized water, and mixed evenly to obtain a polycationic droplet; under a stirring state at a speed of 400-1500r / min, the cationic droplet is added to the second kettle bottom mixed liquid, and the polycationic long-chain branched dispersant is obtained after being kept warm for 2 hours;

[0055] Step 3 is to mix the polyanionic long-chain branched dispersant with the polycationic long-chain branched dispersant to obtain the iron tailings ultrafine sand composite dispersant.

[0056] Example 2

[0057] A method for preparing a composite dispersant for ultrafine sand of iron tailings comprises the following steps:

[0058] Step 1 is to prepare a polyanionic long-chain branched dispersant: 60g of allyl polyoxyethylene ether and 1.5g of 35% hydrogen peroxide are added to 60g of deionized water, and mixed evenly to obtain a first kettle bottom mixed liquid; 4g of acrylic acid, 2g of 2-hydroxyethyl methacrylate phosphate, 3g of 2-acrylamide-2-methylpropane sulfonic acid, 0.15g of Vc and 0.1g of mercaptopropionic acid are added to 30g of deionized water, and mixed evenly to obtain a polyanionic droplet; under stirring at a speed of 400-1500r / min, the polyanionic droplet is dropwise added to the first kettle bottom mixed liquid, and the polyanionic long-chain branched dispersant is obtained after being kept warm for 2 hours;

[0059] Step 2 is to prepare a polycationic long-chain branched dispersant: 60g of allyl polyoxyethylene ether and 1.5g of 35% hydrogen peroxide are added to 60g of deionized water, and mixed evenly to obtain a second kettle bottom mixed liquid; 5g of methyl-acryloyloxyethyl trimethylammonium chloride, 3g of acrylamide, 0.1g of Vc and 0.12g of mercaptopropionic acid are added to 30g of deionized water, and mixed evenly to obtain a polycationic droplet; under stirring at a speed of 400-1500r / min, the cationic droplet is added to the second kettle bottom mixed liquid, and the polycationic long-chain branched dispersant is obtained after being kept warm for 2 hours;

[0060] Step 3 is to mix the polyanionic long-chain branched dispersant with the polycationic long-chain branched dispersant to obtain the iron tailings ultrafine sand composite dispersant.

[0061] Example 3

[0062] A method for preparing a composite dispersant for ultrafine sand of iron tailings comprises the following steps:

[0063] Step 1 is to prepare a polyanionic long-chain branched dispersant: 60g of allyl polyoxyethylene ether and 1.5g of 35% hydrogen peroxide are added to 60g of deionized water, and mixed evenly to obtain a first kettle bottom mixed liquid; 4g of acrylic acid, 2g of blocked amide phosphate, 3g of 2-acrylamide-2-methylpropane sulfonic acid, 0.15g of Vc and 0.1g of mercaptoethanol are added to 30g of deionized water, and mixed evenly to obtain a polyanionic droplet; under a stirring state at a speed of 400-1500r / min, the polyanionic droplet is dropwise added to the first kettle bottom mixed liquid, and the polyanionic long-chain branched dispersant is obtained after being kept warm for 2 hours;

[0064] Step 2 is to prepare a polycationic long-chain branched dispersant: 60g of allyl polyoxyethylene ether and 1.5g of 35% hydrogen peroxide are added to 60g of deionized water, and mixed evenly to obtain a second kettle bottom mixed liquid; 5g of dimethyldiallylammonium chloride, 3g of acrylamide, 0.1g of Vc and 0.12g of mercaptoethanol are added to 30g of deionized water, and mixed evenly to obtain a polycationic droplet; under stirring at a speed of 400-1500r / min, the cationic droplet is added to the second kettle bottom mixed liquid, and the polycationic long-chain branched dispersant is obtained after being kept warm for 2 hours;

[0065] Step 3 is to mix the polyanionic long-chain branched dispersant with the polycationic long-chain branched dispersant to obtain the iron tailings ultrafine sand composite dispersant.

[0066] Comparative Example 1

[0067] A method for preparing a polyanionic long-chain branched dispersant comprises the following steps:

[0068] Add 60g of allyl polyoxyethylene ether and 1.5g of 35% hydrogen peroxide into 60g of deionized water, mix well to obtain a mixed liquid at the bottom of the kettle, add 4g of acrylic acid, 2g of vinyl phosphate, 3g of vinyl sulfonic acid, 0.15g of Vc and 0.1g of mercaptoethanol into 30g of deionized water, mix well to obtain a polyanion dropwise solution, add the polyanion dropwise solution dropwise into the mixed liquid at the bottom of the kettle under stirring at a speed of 400-1500r / min, and keep warm for 2 hours to obtain a polyanion long-chain branched dispersant.

[0069] Comparative Example 2

[0070] A method for preparing a polycationic long-chain branched dispersant comprises the following steps:

[0071] Add 60g of allyl polyoxyethylene ether and 1.5g of 35% hydrogen peroxide to 60g of deionized water, mix well to obtain a mixed liquid at the bottom of the kettle, add 5g of DMDAAC, 3g of acrylamide, 0.1g of Vc and 0.12g of mercaptoethanol to 30g of deionized water, mix well to obtain a polycationic drop solution, add the cationic drop solution dropwise to the mixed liquid at the bottom of the kettle under stirring at a speed of 400-1500r / min, and keep warm for 2 hours to obtain a polycationic long-chain dispersant.

[0072] Comparative Example 3

[0073] A method for preparing a zwitterionic long-chain branched dispersant comprises the following steps:

[0074] Add 120g of allyl polyoxyethylene ether and 3g of 35% hydrogen peroxide to 120g of deionized water, mix well to obtain a mixed solution at the bottom of the kettle, add 4g of acrylic acid, 2g of vinyl phosphate, 3g of vinyl sulfonic acid, 5g of DMDAAC, 3g of acrylamide, 0.25g of Vc and 0.22g of mercaptoethanol to 60g of deionized water, mix well to obtain a mixed drop solution, add the drop solution to the mixed solution at the bottom of the kettle under stirring at a speed of 400-1500r / min, and keep warm for 2 hours to obtain a zwitterionic long-chain branched dispersant.

[0075] Comparative Example 4

[0076] A method for preparing an ultrafine sand dispersant for iron tailings comprises the following steps:

[0077] Step 1 is to prepare a polyanionic dispersant: 60g of allyl polyoxyethylene ether (molecular weight 2700) and 1.5g of 35% hydrogen peroxide are added to 60g of deionized water, and mixed evenly to obtain a first kettle bottom mixed liquid; 4g of acrylic acid, 2g of vinyl phosphate, 3g of vinyl sulfonic acid, 0.15g of Vc and 0.1g of mercaptoethanol are added to 30g of deionized water, and mixed evenly to obtain a polyanionic droplet; under stirring at a speed of 400-1500r / min, the polyanionic droplet is added to the first kettle bottom mixed liquid, and the polyanionic dispersant is obtained after being kept warm for 2 hours;

[0078] Step 2 is to prepare a polycationic dispersant: 60g of allyl polyoxyethylene ether (molecular weight 2700) and 1.5g of 35% hydrogen peroxide are added to 60g of deionized water, and mixed evenly to obtain a second kettle bottom mixed liquid; 5g of DMDAAC, 3g of acrylamide, 0.1g of Vc and 0.12g of mercaptoethanol are added to 30g of deionized water, and mixed evenly to obtain a polycationic drop solution; under a stirring state at a speed of 400-1500r / min, the cationic drop solution is added dropwise to the second kettle bottom mixed liquid, and the polycationic dispersant is obtained after being kept warm for 2 hours;

[0079] Step 3 is to mix the polyanionic dispersant with the polycationic dispersant to obtain the iron tailings ultrafine sand composite dispersant.

[0080] like Figure 1 As shown, the mineral components of the iron tailings ultrafine sand are mainly quartz, hematite and goethite, kaolinite and amphibole. Since the components of the iron tailings ultrafine sand include both substances with positive charges on the surface (hematite and goethite) and substances with negative charges on the surface (silicon dioxide), the two substances are easily attracted together due to electrical properties and are difficult to disperse. The present invention prepares a multi-anion long-chain branched efficient dispersant for the positively charged substances and a multi-cation long-chain branched efficient dispersant for the negatively charged substances, which are easier to adsorb to the surface of the tailings mud particles under Brownian motion and form steric hindrance, making them easier to disperse. The mechanism is as follows Figure 2-3 shown.

[0081] Experimental method: The concrete slump and expansion tests are all based on GB8076 "Concrete Admixtures", and the inverted slump cone time is based on GB50080 "Test Methods for Properties of Ordinary Concrete Mixtures". The mix ratio is shown in Table 1, where tailings mud completely replaces fine aggregate in concrete.

[0082] Table 1 Concrete mix ratio (kg / m 3 )

[0083]

[0084] Table 2 Test results

[0085]

[0086] Note: The amount of dispersant is the amount required to achieve the same concrete expansion / slump, with a solid content of 40%.

[0087] Examples 1-3 are long-chain high-efficiency dispersants of composite polyanions and polycations prepared for substances with positive and negative charges on the surface of the present invention, which are more easily adsorbed to the surface of ultrafine sand particles of iron tailings under Brownian motion and form steric hindrance, making them easier to disperse, so the dosage is small and the concrete viscosity is low.

[0088] In Comparative Example 1 and Comparative Example 2, there is only a single component of dispersant, that is, the polyanionic long-chain branched high-efficiency dispersant only targets substances with positive charges on the surface, and the polycationic dispersant only targets substances with negative charges on the surface. In the composition of this iron tailings ultrafine sand, since the content of positively charged substances in the iron tailings ultrafine sand is about 2-3 times that of negatively charged substances, the amount added in Comparative Example 2 is much greater than that in Comparative Example 1.

[0089] In comparative example 3, Figure 4 As shown in the figure, zwitterionic long-chain branched dispersants easily form "bridge structures" between tailings particles, which not only reduce the steric dispersion effect but also increase the resistance to relative movement between tailings particles, resulting in the concrete system configured with iron tailings ultrafine sand not only failing to reduce the amount of admixture but also leading to an increase in concrete viscosity.

[0090] In Comparative Example 4, Figure 5 As shown, the length of the side chain is shorter than that of Example 1, so the steric hindrance dispersion effect is also smaller than that of Example 1, and it cannot be well dispersed, resulting in the iron tailings ultrafine sand particles being closer and the viscosity of the concrete system increasing.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite dispersant for ultrafine sand of iron tailings, characterized in that: The iron tailings ultrafine sand composite dispersant comprises a polyanionic long-chain branched dispersant and a polycationic long-chain branched dispersant; The polyanionic long-chain branched dispersant is made from the following raw materials in parts by weight: Allyl polyoxyethylene ether 30-60 parts, Peroxide initiator 0.8-2 parts, 2-10 parts of unsaturated organic acid, Phosphate unsaturated monomer 0.1-5 parts, 0.1-5 parts of sulfonic acid unsaturated monomer, Reducing agent 0.05-0.2 parts, Chain transfer agent 0.1-0.4 parts; The polycationic long-chain branched dispersant is made from the following raw materials in parts by weight: Allyl polyoxyethylene ether 30-60 parts, Peroxide initiator 0.8-2 parts, 2-10 parts of cationic unsaturated monomer, 2-5 parts of nonionic unsaturated monomer, Reducing agent 0.05-0.2 parts, Chain transfer agent 0.1-0.4 parts.

2. The iron tailings ultrafine sand composite dispersant according to claim 1, characterized in that: The molecular weight of the allyl polyoxyethylene ether is 4000-5000.

3. The iron tailings ultrafine sand composite dispersant according to claim 1, characterized in that: The peroxide initiator is at least one of hydrogen peroxide, ammonium persulfate or potassium persulfate; the concentration of the hydrogen peroxide is 15-35%; the unsaturated organic acid is at least one of acrylic acid, itaconic acid, maleic acid or fumaric acid; the phosphate unsaturated monomer is at least one of vinyl phosphate, 2-hydroxyethyl methyl acrylate phosphate or blocked amide phosphate; the sulfonic acid unsaturated monomer is vinyl sulfonic acid and / or 2-acrylamide-2-methylpropane sulfonic acid; the reducing agent is at least one of Vc, ferrous sulfate or sodium bisulfite; and the chain transfer agent is mercaptoethanol and / or mercaptopropionic acid.

4. The iron tailings ultrafine sand composite dispersant according to claim 1, characterized in that: The cationic unsaturated monomer is dimethyldiallylammonium chloride and / or methyl-acryloyloxyethyltrimethylammonium chloride; the nonionic unsaturated monomer is acrylamide and / or N,N-dimethylacrylamide.

5. The method for preparing the composite dispersant for ultrafine sand of iron tailings according to any one of claims 1 to 4, characterized in that: The steps include: Step 1 is to prepare a polyanionic long-chain branched dispersant: allyl polyoxyethylene ether and a peroxide initiator are added to deionized water, and mixed evenly to obtain a first kettle bottom mixed liquid; unsaturated organic acid, phosphate unsaturated monomer, sulfonic acid unsaturated monomer, reducing agent and chain transfer agent are added to deionized water, and mixed evenly to obtain a polyanionic dropwise solution; under stirring, the polyanionic dropwise solution is added dropwise to the first kettle bottom mixed liquid, and the polyanionic long-chain branched dispersant is obtained after heat preservation; Step 2 is to prepare a polycationic long-chain branched dispersant: allyl polyoxyethylene ether and a peroxide initiator are added to deionized water, and mixed evenly to obtain a second kettle bottom mixed liquid; a cationic unsaturated monomer, a nonionic unsaturated monomer, a reducing agent and a chain transfer agent are added to deionized water, and mixed evenly to obtain a polycationic dropwise solution; under stirring, the polycationic dropwise solution is added dropwise to the second kettle bottom mixed liquid, and the polycationic long-chain branched dispersant is obtained after heat preservation; Step 3 is to mix the polyanionic long-chain branched dispersant with the polycationic long-chain branched dispersant to obtain the iron tailings ultrafine sand composite dispersant.

6. The method for preparing the composite dispersant for ultrafine sand of iron tailings according to claim 5, characterized in that: In step 1, during the preparation of the first kettle bottom mixed liquid, the mass ratio of allyl polyoxyethylene ether, peroxide initiator and deionized water is 30-60:0.8-2:30-100; in step 1, during the preparation of the polyanion dropwise liquid, the mass ratio of unsaturated organic acid, phosphate unsaturated monomer, sulfonic acid unsaturated monomer, reducing agent, chain transfer agent and deionized water is 2-10:0.1-5:0.1-5:0.05-0.2:0.1-0.4:10-30.

7. The method for preparing the composite dispersant of iron tailings ultrafine sand according to claim 5, characterized in that: In step 2, during the preparation of the second kettle bottom mixed liquid, the mass ratio of allyl polyoxyethylene ether, peroxide initiator and deionized water is 30-60:0.8-2:30-100; in step 2, during the preparation of the polycationic dropwise liquid, the mass ratio of cationic unsaturated monomer, nonionic unsaturated monomer, reducing agent, chain transfer agent and deionized water is 2-10:2-5:0.05-0.2:0.1-0.4:10-30.

8. The method for preparing the composite dispersant for ultrafine sand of iron tailings according to claim 5, characterized in that: The stirring step in step 1 has a rotation speed of 400-1500 r / min, the dropping step time is 1.5-3.5 hours, and the insulation step time is 2 hours; the stirring step in step 2 has a rotation speed of 400-1500 r / min, the dropping step time is 1.5-3.5 hours, and the insulation step time is 2-3 hours.

9. The method for preparing the composite dispersant of iron tailings ultrafine sand according to claim 5, characterized in that: The mass ratio of the polyanionic long-chain branched dispersant to the polycationic long-chain branched dispersant in step 3 is 1-10:1.

Citation Information

Patent Citations

  • Preparation method of mud-resistant polycarboxylic acid water-reducing agent

    CN106589253A

  • Amphoteric early-strength polycarboxylate superplasticizer mother solution for C30 concrete

    CN110305262A